Challenges of multidimensional science education: A philosophical perspective - Verawati, Ni Nyoman Sri Putu; Sarjan, Muhammad (Jurnal Pijar Mipa, 2023)
This study explores multidimensional science education's challenges and critically reviews philosophical aspects. The exploratory study was conducted by performing bibliometric analysis and literature reviews on the context related to the challenges of multidimensional science education from a philosophical perspective. Using data sources from SCOPUS and GOOGLE SCHOLAR, studies were found that align with multidimensional science education (studies that intersect with the application of disciplinary, multi-disciplinary, inter-disciplinary, and trans-disciplinary approaches). The literature review revealed challenges in science education, primarily related to pedagogical challenges. These pedagogical challenges are caused by the interdisciplinary nature inherent in science, thus requiring adequate adaptation of teachers' knowledge about science. The literature review uncovered effective pedagogy in science characterized by approaches that prioritize exploratory processes, authenticity, and a focus on encouraging critical thinking. In line with the principles of axiological philosophy in multidimensional science education, it is essential to prepare adequate pedagogical infrastructure to continue supporting efforts in developing contemporary and future science education. Ultimately, formulating effective pedagogy will serve as a foundation for teachers to impart meaningful and valuable science education from the perspective of axiological philosophy.